1978
DOI: 10.1128/iai.22.2.382-386.1978
|View full text |Cite
|
Sign up to set email alerts
|

Role of bacterial products in periodontitis: humoral immune response to Eikenella corrodens

Abstract: Eikenella corrodens can induce periodontitis-like disease in gnotobiotic rats. Some components of this bacterial cell elicit measurable humoral immune response during the development of the disease, but in this system endotoxin is not among the efficient immunogens. Because no humoral immune response could be seen to the endotoxin of Eikenella corrodens it is assumed that this endotoxin can act uncontrolled in monoinfected rats. Accordingly, the lack of protective humoral immune response to pathogenic componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…The data of others and our earlier publications (13,14), as well as those reported here, support our assumption that antibodies can provide a protective mechanism which may in part be the result of reduced mucosal penetrability of bacterial antigens. In an elegant study, Brandtzaeg and Tolo (3) showed that the excised mucosal membranes of previously immunized rabbits exhibited reduced transfer of the homologous antigen.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The data of others and our earlier publications (13,14), as well as those reported here, support our assumption that antibodies can provide a protective mechanism which may in part be the result of reduced mucosal penetrability of bacterial antigens. In an elegant study, Brandtzaeg and Tolo (3) showed that the excised mucosal membranes of previously immunized rabbits exhibited reduced transfer of the homologous antigen.…”
Section: Resultssupporting
confidence: 92%
“…We also reported that in the same monoinfected rat system the humoral immune response to the monoinfecting agent reduced the bone loss and immunosuppressive irradiation and accelerated the alveolar bone resorption (14).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…A variety of immunoassays have been used to determine levels of systemic and/or local antibody to subgingival bacterial species in subjects with different forms of periodontal disease or periodontal health. These include immunofluorescence (32,38), hemag-glutination (10,24), radioimmunoassay (18,21,46,47), immunodiffusion in gels (42) and enzyme-linked immunosorbent assay (ELISA) (1, 10-17, 20, 23, 25, 28, 31, 36, 37, 40, 45, 51, 53, 54). ELISA has been the method of choice for numerous investigators due to its sensitivity and to its ability to evaluate antibody to a variety of antigens in large numbers of samples.…”
mentioning
confidence: 99%
“…This situation, according to Tanner and coworkers (24), may indicate that the etiological agent is highly virulent; E. (orrodens is recovered in high numbers relative to the other microorganisms in these sites and may thus be a major contributor to the disease process. The periodontopathic nature of E. corrodens in animal model systems has been firmly established by studies showing that oral colonization of E. (corrodens in gnotobiotic rats results in severe periodontal attachment loss within a matter of weeks (9,11).…”
mentioning
confidence: 99%